Deep learning model on rates of change for multi-step ahead streamflow forecasting - Tan, Woon Yang; Lai, Sai Hin; Kumar, Pavitra; Teo, Fang Yenn; Ahmed, El-Shafie (IWA Publishing, 2023)
Water security and urban flooding have become major sustainability issues. This paper presents a novel method to introduce rates of change as the state-of-the-art approach in artificial intelligence model development for sustainability agenda. Multi-layer perceptron (MLP) and deep learning long short-term memory (LSTM) models were considered for flood forecasting. Historical rainfall data from 2008 to 2021 at 11 telemetry stations were obtained to predict flow at the confluence between Klang River and Ampang River. The initial results of MLP yielded poor performance beneath normal expectations, which was R ¼ 0.4465, MAE ¼ 3.7135, NSE ¼ 0.1994 and RMSE ¼ 8.8556. Meanwhile, the LSTM model generated a 45% improvement in its R-value up to 0.9055. Detailed investigations found that the redundancy of data input that yielded multiple target values had distorted the model performance. Qt was introduced into input parameters to solve this issue, while Qtþ0.5 was the target value. A significant improvement in the results was detected with R ¼ 0.9359, MAE ¼ 0.7722, NSE ¼ 0.8756 and RMSE ¼ 3.4911. When the rates of change were employed, an impressive improvement was seen for the plot of actual vs. forecasted flow. Findings showed that the rates of change could reduce forecast errors and were helpful as an additional layer of early flood detection.